(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Gastric ulcer healing is impaired in both hypothyroid and hyperthyroid conditions. Thyroid hormones regulate growth, energy metabolism and mitochondrial oxidative metabolism. Xenobiotics have been documented to negatively impact the thyroid gland at high doses but the redox and cellular interactions at low doses during wound healing process remains unclear. Potassium bromate has been documented to be toxic at high doses but there is dearth of information on its activities at a low dose in varied thyroid states which was evaluated in this study. 60 male Wistar rats (g, n=10) were randomised into 2 conditions: Normal, ulcerated untreated, ulcerated treated with 12.5mg/kg p.o KBrO3 and thyroidectomised groups: thyroidectomised ulcerated, thyroidectomised ulcer treated with KBrO3 and thyroidectomised treated with thyroxine (100µg/kg) Total thyroidectomy was used to model hypothyroidism, and ischaemia-reperfusion-induced gastric ulcers were monitored for healing. Daily body weights, Levels of thyroxine, Gastric mucin content, redox and sodium pump activity were examined alongside other markers of hepatic and haematological toxicity by days 3 and 7 post ulceration. Data were analysed using descriptive statistics and ANOVA α 0.05. The bromate-exposed hypothyroid rats showed increased gastric ulcer healing potential with reduced gastric epithelial oedema and inflammation; hepatic steatosis, and periportal inflammation. Haematological variables and markers of hepatic functions were normal. There were reduced levels of gastric and hepatic malondialdehyde levels. Thyroxine and potassium bromate treatment resolved the redox and cellular toxicity possibly via increasing catalase and sulfhydryl levels and increased Na+ K+ pump activity. We conclude that potassium bromate enhanced gastric ulcer healing in hypothyroid state, similar to thyroxine treatment.